2021
DOI: 10.1038/s41598-021-90038-4
|View full text |Cite
|
Sign up to set email alerts
|

Grain Fe and Zn content, heterosis, combining ability and its association with grain yield in irrigated and aerobic rice

Abstract: Genetic improvement of rice for grain micronutrients, viz., iron (Fe) and zinc (Zn) content is one of the important breeding objectives, in addition to yield improvement under the irrigated and aerobic ecosystems. In view of developing genetic resources for aerobic conditions, line (L) × tester (T) analysis was conducted with four restorers, four CMS lines and 16 hybrids. Both hybrids and parental lines were evaluated in irrigated and aerobic field conditions for grain yield, grain Fe and Zn content. General C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 50 publications
(60 reference statements)
2
8
0
Order By: Relevance
“…Accordingly, the genetic variations that were discovered could be exploited in establishing a successful rice program for breeding high-yielding and drought-tolerant genotypes. In keeping with these findings, high genetic variations have also been observed for different agronomic traits in rice under well-watered and water-deficit conditions by Venuprasad et al [ 49 ], Monkham et al [ 50 ], Khan et al [ 2 ], and Anusha et al [ 17 ]. The significant difference between tested irrigation regimes resulted in dissimilar impacts on the evaluated genotypes.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…Accordingly, the genetic variations that were discovered could be exploited in establishing a successful rice program for breeding high-yielding and drought-tolerant genotypes. In keeping with these findings, high genetic variations have also been observed for different agronomic traits in rice under well-watered and water-deficit conditions by Venuprasad et al [ 49 ], Monkham et al [ 50 ], Khan et al [ 2 ], and Anusha et al [ 17 ]. The significant difference between tested irrigation regimes resulted in dissimilar impacts on the evaluated genotypes.…”
Section: Discussionsupporting
confidence: 58%
“…They disclosed that the additive gene effects contribute considerably to the inheritance of grain yield and several related traits in rice. On the contrary, other reports have found that non-additive gene action has a major role in the inheritance of agronomic traits in rice [ 17 , 19 , 75 ]. The significant GCA × I and SCA × I interactions for grain yield and most of the other studied traits indicate the differential performance of the parental genotypes and hybrids under distinct conditions.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…This could have negative effects on plant growth and where crops are concerned could impact negatively on human or animal health. This is particularly serious in the case of iron (Fe) and zinc (Zn) where around 60% and 30% of the world population suffer from deficiency of these two minerals (Anusha et al ., 2021). Accordingly, decreased accumulation of these elements in fodder crops or cereals for human consumption could have serious health consequences and are likely to exacerbate what has been referred to as ‘hidden hunger’, prevalent particularly in the countries of sub‐Saharan Africa (Gashu et al ., 2021).…”
Section: Introductionmentioning
confidence: 99%